Early and Long-Term HIV-1 Immunogenicity Induced in Macaques by the Combined Administration of DNA, NYVAC and Env Protein-Based Vaccine Candidates: The AUP512 Study - Perdiguero, Beatriz; Asbach, Benedikt; Gómez, Carmen E.; Köstler, Josef; Barnett, Susan W.; Koutsoukos, Marguerite; Weiss, Deborah E.; Cristillo, Anthony D.; Foulds, Kathryn E.; Roederer, Mario; Montefiori, David C.; Yates, Nicole L.; et al. (Frontiers in Immunology, 2022)
To control HIV infection there is a need for vaccines to induce broad, potent and long-term B and T cell immune responses. With the objective to accelerate and maintain the induction of substantial levels of HIV-1 Env-specific antibodies and, at the same time, to enhance balanced CD4 and CD8 T cell responses, we evaluated the effect of concurrent administration of MF59-adjuvanted Env protein together with DNA or NYVAC vectors at priming to establish if early administration of Env leads to early induction of antibody responses. The primary goal was to assess the immunogenicity endpoint at week 26. Secondary endpoints were (i) to determine the quality of responses with regard to RV144 correlates of protection and (ii) to explore a potential impact of two late boosts. In this study, five different prime/boost vaccination regimens were tested in rhesus macaques. Animals received priming immunizations with either NYVAC or DNA alone or in combination with Env protein, followed by NYVAC + protein or DNA + protein boosts. All regimens induced broad, polyfunctional and well-balanced CD4 and CD8 T cell responses, with DNA-primed regimens eliciting higher response rates and magnitudes than NYVAC-primed regimens. Very high plasma binding IgG titers including V1/V2 specific antibodies, modest antibody-dependent cellular cytotoxicity (ADCC) and moderate neutralization activity were observed. Of note, early administration of the MF59-adjuvanted Env protein in parallel with DNA priming leads to more rapid elicitation of humoral responses, without negatively affecting the cellular responses, while responses were rapidly boosted after repeated immunizations, indicating the induction of a robust memory response. In conclusion, our findings support the use of the Env protein component during priming in the context of an heterologous immunization regimen with a DNA and/or NYVAC vector as an optimized immunization protocol against HIV infection.